Design and Evaluation of Ezetimibe Rapidmelts by Direct Compression and Sublimation Methods (Asian Journal of Pharmaceutics (AJP), 2016)
Aim: The aim of this study was to formulate and evaluate ezetimibe rapidmelts by sublimation and direct compression techniques. Materials and Methods: As ezetimibe comes under Class II drug, the solubility of the drug should be increased before formulation. For that, solid dispersions were prepared with Î²-CD and pvp k-30 using coevaporation and kneading methods. Among those solid dispersions prepared with Î²-CD (1:1.5) using coevaparation method has given better drug entrapment values compared to other solid dispersions. Those solid dispersions were formulated as rapidmelts using direct compression. In direct compression method, rapidmelts were prepared using superdisintegrants such as crospovidone, croscaramellose sodium, and starch 1500. Those are evaluated for both pre- and post-compression parameters. Ezetimibe rapidmelts were prepared by sublimation method using subliming agents camphor, urea, and ammonium bicarbonate. Each subliming agent is used in three different concentrations (2.5, 5.0, 7.5%). Results and Discussion: Rapidmelts prepared with the two methods were evaluated for weight variation, hardness, friability, % drug content, and disintegration time. The best formulation was subjected to stability testing for 6 months at 25Â°C/60% RH and 40Â°C/75% RH. All the prepared formulations compiled with the pharmacopeial limits. Conclusion: The results suggest that E12 formulation has given the best disintegration and dissolution results. From the result, it was concluded that rapidmelts prepared using sublimation method had given better result than direct compression method. That final formulation was further evaluated for in-vivo studies.